N-Acetylcysteine, N-Acetylcysteine Amide, and Thioredoxin Mimetic Peptides Regenerate Mercaptoalbumin and Exhibit Antioxidant Activity - Sonia Eligini; Marco Munno; Gloria Modafferi; Daphne Atlas; Cristina Banfi (MDPI AG, 2024)
Albumin (HSA) is the most abundant circulating protein and plays a pivotal role in maintaining the redox state of the plasma. Three HSA proteoforms have been identified based on the redox state of cysteine 34. These proteoforms comprise of the reduced state (HSA-SH) referred to as mercaptoalbumin, non-mercaptoalbumin-1, containing a disulfide with small thiols such as cysteine (HSA-Cys), and non-mercaptoalbumin-2, representing the higher oxidized proteoform. Several clinical studies have shown a relationship between an individual's serum HSA redox status and the severity of diseases such as heart failure, diabetes mellitus, and liver disease. Furthermore, when HSA undergoes oxidation, it can worsen certain health conditions and contribute to their advancement. This study aimed to evaluate the ability of the redox compounds AD4/NACA and the thioredoxin mimetic (TXM) peptides TXM-CB3, TXM-CB13, and TXM-CB30 to regenerate HSA-SH and to enhance its redox activity. The HSA proteoforms were quantified by LC-MS, and the antioxidant activity was determined using dichlorofluorescin. Each of the compounds exhibited a significant increase in HSA-SH and a reduction in HSA-Cys levels. The increase in HSA-SH was associated with a recovery of its antioxidant activity. In this work, we unveil a novel mechanistic facet of the antioxidant activity of AD4/NACA and TXM peptides. These results suggest an additional therapeutic approach for addressing oxidative stress-related conditions.